The Influence of Firm Size, Marketing Strategy and Market Research Activities on the Export Performance of Small and Medium Sized Manufacturers in Malaysia - Ismail, Noor Azlin (2003)
The main purpose of this study is to identify the influence of firm size. marketing strategy and market research activities on the export performance among Small and Medium Industries (SMIs) in Malaysia. Industries involved in this study were food processing (food industry), rubber and related products, and chemical and related products (other industries). The specific objectives of this study were to determine if there is existed a relationship between firm size, marketing strategy and market research activities on the export performance, and how these variables influence the performance among SMI manufacturers in different industry in Malaysia. A total of two hundred twenty (220) respondents in Peninsular Malaysia are selected as a population for this study. From the number, only 65 sets of questionnaires are usable to be analyzed for the study. The instruments to measure independent and dependent variables are adapted from the studies done by Wolff and Pett 2000), Sh6ham (1 999), and Hart and Tzoka (1999). SPSS version 11.0 and LlSREL Statistical Packages were used to analyze the data of the study. The finding of this study by using inferential analysis is valid only for food industry. The main reason was due to small sample size from other industries. As such the comparative study for both industries are only valid for descriptive analysis. From the multiple regression result, the study indicates that, for food industry (consumer products), firm size and marketing strategy were found to be negatively related with export performance and market research activities was positively related with export performance. However, the findings of this study revealed that, the influence of firm size, marketing strategy and market research activities on the export performance vary among the different types of products manufactured; i.e. consumer or industrial products.